2003
DOI: 10.1081/ddc-120018375
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of the Flavonoid Quercetin in Rats After Single Intravenous and Oral Doses

Abstract: The pharmacokinetic and mean time tissue distribution parameters, after a single 50-mg/kg dose of quercetin administered as intravenous bolus, oral solution, and oral suspension, were determined using rat as an animal model. Following intravenous administration, the elimination rate constant and the elimination half-life were found to be 0.0062 min(-1) and 111 min, respectively. Examining the mean time tissue distribution parameters reflected a strong binding affinity of the drug molecules to both plasma and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 25 publications
1
44
2
Order By: Relevance
“…1 Using a dose of 100 mmoles kg À1 twice daily, one would anticipate that plasma quercetin levels would peak at higher levels than when a dose of 25 mmoles kg À1 was administered thrice daily. It is known that quercetin, in solution administered intravenously in the rat, has a biphasic plasma clearance with a rapid drop in concentration followed by a slower drop with a half-life of 111 min with an intrinsic mean residence time within peripheral tissues of just over 3 h. 14 In our investigations, quercetin is administered intraperitoneally in the form of a suspension in saline. The work of Khaled and colleagues 14 has demonstrated that quercetin administered as a suspension takes 50% longer time to enter plasma than quercetin administered in solution; hence, one might anticipate a longer quercetin residence time in tissues that may affect therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 93%
“…1 Using a dose of 100 mmoles kg À1 twice daily, one would anticipate that plasma quercetin levels would peak at higher levels than when a dose of 25 mmoles kg À1 was administered thrice daily. It is known that quercetin, in solution administered intravenously in the rat, has a biphasic plasma clearance with a rapid drop in concentration followed by a slower drop with a half-life of 111 min with an intrinsic mean residence time within peripheral tissues of just over 3 h. 14 In our investigations, quercetin is administered intraperitoneally in the form of a suspension in saline. The work of Khaled and colleagues 14 has demonstrated that quercetin administered as a suspension takes 50% longer time to enter plasma than quercetin administered in solution; hence, one might anticipate a longer quercetin residence time in tissues that may affect therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 93%
“…19) In our preliminary experiment, the bioavailability of quercetin dissolved in dimethylsulfoxide/water (70 : 30) solution in rats was 3.2-fold higher than that of quercetin suspended in water. Thus, the solubility of quercetin is a highly important factor for its bioavailability.…”
Section: Fig 3 Pharmacokinetic Profile Of Quercetin (A) Isorhamnetmentioning
confidence: 99%
“…Due to the low water solubility of quercetin, it has a minimal absorption in the gastrointestinal tract, and its oral bioavailability is lower than 17% in rats [6] and lower than 1% in humans [7]. Different approaches have been proposed in literature to increase the bioavailability of quercetin.…”
Section: (Figure 1)mentioning
confidence: 99%